Automation of (SCM) information systems and its impact on creative operational performance - Study a sample of companies in: Setif and M’sila - merouani, rabeh (Journal of Research in Finance and Accounting, 2022)
This study was conducted to find out the extent to which automation has been adopted in information systems (SCM) for some companies in: Setif and M’sila, through an electronic network enhanced with (SCP, SCE) software to manage supplies of materials and deliveries, as well as to know the impact of this automation on the creative performance of supply operations. This study showed that there is a real benefit from the advantages of automation in the information systems (SCM), existing in the surveyed companies, which led to the emergence of a kind of creative operational performance, such as: improving the effectiveness of purchasing, storing and integrating materials, as well as improving the effectiveness of handling, design and delivery towards clients.